Variable thermal conductivity and mass diffusivity effects in a free convective flow of doubly stratified non-darcian porous medium over a vertical plate - Suganthi, R.K.; Pullepu, Bapuji; Supriya, P.; Shanmugapriya, M.; Pop, I. (Zielona Góra: Uniwersytet Zielonogórski)
The research in this article is carried out to study incompressible and unsteady free convective flow on a semi- infinite isothermal vertical plate in a doubly stratified non-Darcian porous media with variable mass diffusivity and variable thermal conductivity. The governing non-linear partial differential equations of flow were calculated by applying an implicit finite difference scheme of the Crank-Nicolson type.
Keywords: mass diffusivity; non-Darcy; porous medium; stratification; thermal conductivity